Immunosuppression of Macrophages Underlies the Cardioprotective Effects of CST (Catestatin). Issue 5 (8th April 2021) - Ying, Wei; Tang, Kechun; Avolio, Ennio; Schilling, Jan M.; Pasqua, Teresa; Liu, Matthew A.; Cheng, Hongqiang; Gao, Hong; Zhang, Jing; Mahata, Sumana; Ko, Myung S.; Bandyopadhyay, Gautam; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Hypertension is associated with inflammation and excessive production of catecholamines. Hypertensive patients have reduced plasma levels of CST (catestatin)—a bioactive cleavage product of the prohormone CgA (chromogranin A). In mouse models, hypertension symptoms can be reduced by administration of CST, but the role of CST in the regulation of cardiovascular function is unknown. In this study, we generated mice with KO (knockout) of the region of the CgA gene coding for CST (CST-KO) and found that CST-KO mice are not only hypertensive as predicted but also display left ventricular hypertrophy, have marked macrophage infiltration of the heart and adrenal gland, and have elevated levels of proinflammatory cytokines and catecholamines. Intraperitoneal injection with CST reversed these phenotypes, and ischemic preconditioning-induced cardioprotection was also abolished in CST-KO mice. Experiments with chlodronate depletion of macrophages and bone marrow transfer showed that macrophages produce CST and that the antihypertensive effects of CST are mediated, in part, via CST's immunosuppression of macrophages as a form of feedback inhibition. The data thus implicate CST as a key autocrine attenuator of the cardiac inflammation in hypertension by reducing macrophage inflammation.